Papers of Fred Chaney - Chaney, F. M. (Frederick Michael), 1941- (1953)
MS Acc03.054 comprises a diary, desk calendars, photographs and papers relating to Chaney's legal and political activities in the 1970s (5 boxes, 1 small box).
The Acc03.118 instalment consists of further papers (28 boxes, 21 cartons).
The Acc07.057 instalment includes correspondence, subject files, case files, personal and family papers, speeches, articles and diaries reflecting Chaney's varied political, legal and academic career (99 boxes, 2 fol. items).
The Acc09.046 instalment comprises papers that document Chaney's wide-ranging professional interests and activities. They include correspondence; seminar and lecture papers and speeches; articles; notes; submissions, issues and discussion papers; reports; legal papers; agreements; publications; project and working papers; meetings and board documents; appointment diaries; and press cuttings. Organisations and subjects reflected in the collection include Aboriginal education and employment, Reconciliation Australia, Native Title and Indigenous Land Use, Desert Knowledge Australia, the Aboriginal Legal Service and Bringing Them Home. Amongst the correspondence are letters from politicians including Prime Minister John Howard, from High Court judge Michael Kirby and from others including Marlene Jackamarra, David Ritter, Tim Acker and Hal Wootten. Native Title and Indigenous Land Use documents include those pertaining to Ngaanyatjarra, Wongutha, Yorta Yorta, the Ord, Argyle Diamond and Rio Tinto claims and agreements (36 boxes).
The Acc09.152 instalment includes audio visual and digital material on audiocassettes, CDs, DVDs and CD-ROMs. The sound recordings include an interview on mediation processes (2001); AIATSIS seminar presentations by Fred Chaney and Christa Scholz (undated); and the Hyllus Maris Annual Memorial Lecture (2003). On DVD is a video of the Indigenous Governance Awards finalists from 2005. The digital material includes photographs, powerpoint presentations and word documents (ca. 2004-2005) relating to Chaney's activities as a member of the National Native Title Tribunal. A powerpoint presentation includes images from the Nookenbah (Noonkenbah) Native Title dispute, and of Richard Court and Peter Shergold during negotiation and signing of a Native Title agreement. The digital photographs include images of Ningali Lawford, Fred Chaney and Angela Chaney (1 packet).
The Acc12.108 instalment comprises official papers, assorted newspaper clippings, project proposals and reports, conference papers and lecture notes relating to mining and indigenous issues. Particular subjects reflected include Aboriginal health and education, Reconciliation Australia, Central Desert Native Title, Indigenous Land Management and Desert Knowledge Australia (8 boxes).
Manuscript reference no.: MS Acc03.054, MS Acc03.118, MS Acc07.057, MS Acc09.046, MS Acc09.152, MS Acc12.108.
Associated materials: Papers of Sir Frederick Chaney, 1914-2002 MS 9874.
Cultural sensitivity advisory notice: Aboriginal, Torres Strait Islander and other First Nations people are advised that this collection may contain names, recordings and images of deceased people and other content that may be culturally sensitive. Please also be aware that you may see certain words or descriptions within these works which reflect the author’s attitude, or that of the period in which the works were created, and may now be considered inaccurate, inappropriate or offensive.
Also available online
National Library of Australia Oral History collection ORAL TRC 5000/339.
Lawyer, politician and university chancellor. Frederick Michael (Fred) Chaney was born at Perth, Western Australia in 1941. He practised as a lawyer until he entered Federal Parliament at the 1974 election. He was the Liberal Party Senator for Western Australia from 1974 until 1990, during which time he served as Leader of the Opposition in the Senate, 1983-1990. He then became Member for Pearce in the House of Representatives from 1990 until 1993. He was a member and deputy president of the National Native Title Tribunal, 1994-2007, and chancellor of Murdoch University from 1995-2003. He served as co-chair of Reconciliation Australia Ltd from 2000-2005, and continues as a director on the Board. In 1997 Chaney was appointed an Officer of the Order of Australia (AO) and in 2001 he received a Centenary Medal for service to the Parliament of Australia and education.
Keywords: Chaney, F. M. -- 1941- -- Archives; Liberal Party of Australia -- Officials and employees -- Archives; Murdoch University -- Presidents -- Archives; Reconciliation Australia (Organisation); Politicians -- Australia -- Archives; Lawyers -- Australia -- Archives; College administrators -- Australia -- Archives; Australia -- Politics and government; Federal politicians; Lawyers; Chancellors